The Alchemy of Domination, 2.0?1 A Response to Professor Kecia Ali (American Journal of Islam and Society, 2018)
In her critical essay, “The Omnipresent Male Scholar,”2 Professor Kecia Alisets out to call attention to what she sees as the hegemonic privileging ofthe male scholarly perspective and the need to replace this with an academiclandscape more reflective and accommodating of the experiences andscholarly vantage points of women. To this end, she profiles the works ofseveral (Muslim) men in Islamic Studies (myself included) and highlightsthe various ways in which they omit, overlook, undervalue, or dismiss thetopic of women or the scholarly views and interventions of female scholars.Her arguments are reiterated and expanded (this time without naming hertargets) in her Ismail R. al-Faruqi Memorial Lecture delivered at the 2017annual conference of the American Academy of Religion.3 The present essayaims to respond to Professor Ali’s assessment of my work, most specificallyIslam and the Blackamerican (and to a lesser extent, Islam and theProblem of Black Suffering) alongside some of the broader issues she raisesas part of her general critique. I will leave it to the other male scholars sheprofiles to respond to what she has to say about their work ...